Effects of Dexmedetomidine Postconditioning on Myocardial Ischemia/Reperfusion Injury in Diabetic Rats: Role of the PI3K/Akt-Dependent Signaling Pathway. (8th October 2018) - Cheng, Xiangyang; Hu, Jing; Wang, Ya; Ye, Hongwei; Li, Xiaohong; Gao, Qin; Li, Zhenghong
Abstract : Objective . The present study was designed to determine whether dexmedetomidine (DEX) exerts cardioprotection against myocardial I/R injury in diabetic hearts and the mechanisms involved. Methods . A total of 30 diabetic rats induced by high-glucose-fat diet and streptozotocin (STZ) were randomly assigned to five groups: diabetic sham-operated group (DM-S), diabetic I/R group (DM-I/R), diabetic DEX group (DM-D), diabetic DEX + Wort group (DM-DW), and diabetic Wort group (DM-W). Another 12 age-matched male normal SD rats were randomly divided into two groups: sham-operated group (S) and I/R group (I/R). All rats were subjected to 30 min myocardial ischemia followed by 120 min reperfusion except sham groups. Plasmas were collected to measure the malondialdehyde (MDA), creatine kinase isoenzymes (CK-MB), and lactate dehydrogenase (LDH) levels and superoxide dismutase (SOD) activity at the end of reperfusion. Pathologic changes in myocardial tissues were observed by H-E staining. The total and phosphorylated form of Akt and GSK-3 β protein expressions were measured by western blot. The ratio of Bcl-2/Bax at mRNA level was detected by reverse transcription-polymerase chain reaction (RT-PCR). Results . DEX significantly reduced plasma CK-MB, MDA concentration, and LDH level and increased SOD activity caused by I/R. The phosphorylation of Akt and GSK-3 β was increased, Bcl-2 mRNA and the Bcl-2/Bax ratio was increased, and Bax mRNA was decreased in the DEX group as compared to the I/R group, while posttreatment with Wort attenuated the effects induced by DEX. Conclusion . The results of this study suggest that DEX postconditioning may increase the phosphorylation of GSK-3 β by activating the PI3K/Akt signaling pathway and may inhibit apoptosis and oxidative stress of the myocardium, thus exerting protective effects in diabetic rat hearts suffering from I/R injury.